Transits and indigenous negotiations in Espírito Santo at the time Brazilian Independence: Botocudos Indians between the forests and villages (Ágora Journal, 2022)
In the 19th century, the Botocudos, a group of Brazilian natives, were the target of the continuous contact with Portuguese-Brazilian colonizers interested in the colonization of the Rio Doce (Doce River) region, with actions that ranged from violent attacks to the attempts of pacification and settlement, from Brazilian Independence. In this article, we analyze a set of documents formed by military and native’s directors correspondences written during the dacades of 1820-1830 in Espírito Santo, that documents reveal the impetuous indigenous resistance, not just in a offensive way, but using the resources offered by the colonizers and undertaking a constant transit among the space of the “sertão” (the forests) to the colonizing enclaves formed by barracks, villages and settlements. This analysis allowed us to identify the different Botocudos groups and their self-denominations, their internal rivalries, the domain of the territory and the indigenous awareness of the colonization in the process.
Keywords: Botocudo Indians; colonization; resistance; indigenous protagonism